Profail Pengguna, Amalan dan Kesan Menghisap Vape di Malaysia (Jurnal Pembangunan Sosial, 2017)
Electronic cigarettes also known as vape or vapor have received increasing popularity among the younger generation. Among the main reasons for vaping is to stop and to reduce the harm and ill effect of smoking. In 2015, the National Fatwa Council has declared that vaping is ‘haram’. However, the use is still on the rise. The study aims to examine the user profile, reasons for choosing to vape, usage habits and side effects of its use. The study uses a cross sectional survey design through questionnaire obtaifrom 631 people. The findings show that many vapers are Malays and are still single. Many start vaping on their own, have their own vaping equipment and claim it is easy to buy. Some 37.2% claimed that the number of cigarettes smoked has been reduced. Only a small number admit they mix it with other drugs; 27% want to stop from vaping while more than half is uncertain whether they want to stop vaping. In terms of its effect, 3.96% reported experiencing more than five of the 12 withdrawal effects, such as physical attraction effects (headache and joints); emotional attraction (boredom, frustration and frustration); cognitive effects (hard to think, difficult to make choices and decision making). Implications are discussed in terms of raising awareness especially for Muslims and prevention in general.